Incidence and determinants of low birth weight in Peninsular Malaysia: a multicentre prospective cohort study - Mansor, Elliza; Ahmad, Norliza; MohdZulkefli, NorAfiah; Lim, PohYing (Public Library of Science, 2024)
Background and objective Pregnant mothers are at risk of many adverse pregnancy outcomes, including infants with low birth weight (LBW). The World Health Organization aimed to achieve a 30% reduction in the number of LBW infants by the year 2025. In this study, we aimed to determine the incidence and determinants of LBW infants among pregnant mothers attending government health clinics in Peninsular Malaysia.